O imaginário da mediunidade no processo de escritura em Fernando Pessoa - Medeiros, Alisson Diego Dias de (2012)
The answer to creating a fictional world? Repulsion or form of reaction to an outside world? Mental illness, whose brand can be symbolic simulation or depersonalization? Hard to take a stand when the deed is a poet Fernando Pessoa as what is at stake. Notes Schlafman Léo (1998) who, at the age of 20 years, Fernando Pessoa wrote in English, in his diary, "One of my mental complications is the fear of madness, which in itself already is crazy." What rid of madness, notes Robert Bréchon (1986), was the taste of the game and was playing it for your writing. Even though it has rid the madness, the poet does not quit seeking explanations - or provide it - for the phenomena much bother him, or defined.'s where we come across the alignment of Fernando Pessoa within philosophical as occultism and reading about psychological and mental disorders treated. paths were pursued by him to explain the existence of his heteronyms and its entry process. This work therefore presents main objective: to analyze the personal papers of Fernando Pessoa, whose outstanding feature is the presence of occult and alleged mediumship demonstrations held in response to non-literary and heteronímicas. Therefore, I focused on specific goals, which are: a) to study the speech of Fernando Pessoa on his mediumship / occult b) analyzing specific texts that are, for the poet, psychic demonstrations, c) study of a series of excerpts personal letters in which Fernando Pessoa suggested to be a medium. Admittedly, this essay will touch many arguments already made by scholars and experts of Fernando Pessoa, but consider the possibility of developing issues and contribute to the critical fortune of the poet. We assume that announces the Portuguese scholar Jerome Pizarro (2006), one of the greatest scholars of the work Pessoan: those interested in Fernando Pessoa be lost in the maze created by him. It is the image of a person-Minotaur, devouring all but, holding us in its labyrinthine tessitura, as marked by mystery. Will draw on our analysis, a theory aligned themselves to objects of research, whose main authors are Sigmund Freud (1908) Carl Jung (1991.1996). Gaston Bachelard (1996), Helena Blavatsky (2008), among others